ANALISIS KESULITAN SISWA DALAM MENYELESAIKAN SOAL OPERASI HITUNG ALJABAR KELAS VII DI SMP N 1 2X11 KAYUTANAM - Ratna Yuliani; Isnaniah Isnaniah; Adiarni Nelda (Universitas Pahlawan Tuanku Tambusai, 2022)
Algebra is a very important subject in learning mathematics. One of the algebraic sub-materials in mathematics at junior high school is algebraic arithmetic operations. The purpose of this research is to find out the difficulties and factors that cause students' difficulties in completing algebraic operations. This research was conducted at SMP N 1 2x11 Kayutanam in the odd semester of the 2022/2023 academic year. The subjects in this study were 22 students in class VII-2. In this study, researchers used data collection methods by observation, test descriptions of 8 items, interviews, and documentation. Meanwhile, students' difficulty in completing algebraic arithmetic operations is the difficulty of concepts and principles. teaches the concept of students' difficulties when determining which includes variables, coefficients, constants and many terms. completing principles by students, namely experiencing difficulties in using the principles of addition and subtraction with positive or negative numbers, lack of understanding of students in groupings of similar tribes, lack of thoroughness in doing algebraic addition and subtraction, students' difficulties in adding algebraic operations, and students having difficulties in principles equate the pronunciation of algebraic fractions. The data analysis technique used in this study is data reduction, data presentation, and drawing conclusions. Keywords: Analysis, Student Difficulties, Algebraic Operations